Variáveis climáticas como fatores determinantes da produção de biomassa em floresta tropical seca - Campos, Diego Antunes (2019)
The great variability of rainfall and the drought are inherent properties of semiarid zones and they represent one the most determinant factors of biomass production. Then we aimed identify the long term and trend patterns of rainfall and temperature using temporal patterns of each one; evaluate the during of dry and wet seasons; verify the influence of rain distribution over the aerial plant biomass dynamic in Dry Tropical Forest/Phytogeografic Domain of Caatinga (DTF/PDC). We carried out the experiment in a 40 years regeneration fragment of DTF/PDC, in Ceará, Brazil. We employed daily historical series of precipitation and temperature to evaluate the climatological variables. The annual and monthly climatological normal (1974 – 2018) were calculated using rainfall data, beside consecutive dry days (CDD) in rainy season (hydric deficit). Using the temperature data we calculated the annual average of the maximums, means and minimums (1996 – 2017). We also calculated the Standardized Precipitation Evapotranspiration Index (SPEI). We identified, measured and quantified all living specimens with soil level diameter (SLD) ≥ 3 cm and height (h) ≥ 100 cm in eight basic experimental of 10 x 10 m, for the years of 2009/2010/2015/2016/2018/2019. We estimated the biomass with alometric equation definite for region of DTF/PDC. We found great rainfall interannual variability, with very wet years (1985, 2009 and 2011) and very dry years (1979, 1983 and 1993) interleaved by periods with precipitation around the mean. The class of 5 to 10 days without rain was the most frequent and presented a decrease trend, beside it showed an increase in the trend of the dry days in class of more than 16 days. The annuals maximum temperatures presented increasing trends over the years and the minimum temperatures showed smaller increase. We identified 9 families, 14 genus and 15 species, that no varied over the 11 years. The great number of identified species belongs to Fabaceae and Euphorbiaceae families. Due the mortality of the individuals between 2009 and 2019 occurred a biomass decreasing of 65.33 Mg ha-1 to 44.47 Mg ha-1 respectively, representing a mean biomass reduction of 3.26 Mg ha-1 ano-1. We concluded that the extreme rainfall events are usual and presented alternation between dry and wet years. The last seven years represented the longest period with total annual precipitations below the historical average, however it was not the most intense. The DTF/PDC fragment did not reach the climax even after 40 years in regeneration process. Dry years promoting the tree and shrub mortality, especially those with smaller diametric classes. The biomass production is greatly affected by climatic seasonality with direct relationship with the temporal distribution of rainfall events.